The effect of curvature ratio towards the fluid flow characteristics in bend pipe based on numerical methods - James Julian; Fitri Wahyuni; Waridho Iskandar; Rifqi Ramadhani (Universitas Muhammadiyah Metro, 2023)
Internal flows in pipes are studied in greater depth and comprehensiveness in research. The computation done by using RANS equation. In particular, this study uses two equations turbulence model which is k-ε turbulence model. Mesh with 2×106 element is used because it is a mesh with lowest error. The research focuses on the effect of the curvature ratio (Rc) at the bend on changes in fluid flow characteristics. The Rc variations chosen in this study were 0.01, 0.02, and 0.03. The pipe diameter is 0.01 m, resulting in Rc/D=1, Rc/D=2, and Rc/D=3. At Rc/D=1, the maximum fluid flow velocity is in an area closer to the inner core than the outer core. The fluid velocity distribution is also more even if Rc/D=1 is enlarged. The fluid flow separation appears in the pipe with Rc/D=1, but the fluid flow separation in Rc/D=2 and Rc/D=3 is not visible. The separation is at α=75.96º, while the reattachment location is at x/D=0.014.